2018
DOI: 10.1038/s41598-018-25124-1
|View full text |Cite
|
Sign up to set email alerts
|

UNG-1 and APN-1 are the major enzymes to efficiently repair 5-hydroxymethyluracil DNA lesions in C. elegans

Abstract: In Caenorhabditis elegans, two DNA glycosylases, UNG-1 and NTH-1, and two AP endonucleases, APN-1 and EXO-3, have been characterized from the base-excision repair (BER) pathway that repairs oxidatively modified DNA bases. UNG-1 removes uracil, while NTH-1 can remove 5-hydroxymethyluracil (5-hmU), an oxidation product of thymine, as well as other lesions. Both APN-1 and EXO-3 can incise AP sites and remove 3′-blocking lesions at DNA single strand breaks, and only APN-1 possesses 3′- to 5′-exonulease and nucleot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…The dinoflagellates have both mono-functional and bi-functional glycosylases (Figure 3 and Table 3). The glycosylases targeting uracil and its derivatives including UNG [76], SMUG1 [77], MBD4 [78], TDG [77,78] and NTH1 [79], are of special interest. These genes were reported to have activities against 5hmu.…”
Section: Resultsmentioning
confidence: 99%
“…The dinoflagellates have both mono-functional and bi-functional glycosylases (Figure 3 and Table 3). The glycosylases targeting uracil and its derivatives including UNG [76], SMUG1 [77], MBD4 [78], TDG [77,78] and NTH1 [79], are of special interest. These genes were reported to have activities against 5hmu.…”
Section: Resultsmentioning
confidence: 99%
“…Several years later, the ung-1 and nth -1 genes encoding U racil D N A G lycosylase UNG-1 and E n donuclease III NTH-1, respectively, were identified and characterized in C. elegans ( Nakamura et al, 2008 ; Morinaga et al, 2009 ). Despite several attempts, including extensive homology searches and most importantly enzymatic assays designed to remove specific DNA lesions such as 8-oxoGuanine, no other DNA glycosylases have been found in C. elegans besides UNG-1 and NTH-1 ( Denver et al, 2003 ; Papaluca et al, 2018 ). It seems puzzling that this multicellular organism conserved only two DNA glycosylases when the unicellular E. coli , the budding yeast S. cerevisiae and human cells have conserved eight, five and eleven DNA glycosylases, respectively ( Denver et al, 2003 ; Wallace, 2014 ).…”
Section: Dna Glycosylases In C Elegansmentioning
confidence: 99%
“…Recently, it has been reported that UNG-1 may possess the ability to process the oxidized base lesion 5-hmU. This is based on phenotypic analysis of C. elegans ung-1 mutant showing decreased survival upon exposure to the nucleoside form of 5-hmU ( Papaluca et al, 2018 ). We propose that C. elegans UNG-1, unlike Ung from other organisms, may have evolved to acquire a broader substrate specificity and thus could act as the dominant DNA glycosylase in vivo to remove various modified forms of uracil such as the 5-hmU lesion.…”
Section: Dna Glycosylases In C Elegansmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it has also been proposed that HMdU present in double-helical DNA might cause genomic instability as it can form potentially mutagenic lesions and destabilize double-helical DNA [16]. However, this formation of mutagenic and DNA destabilizing lesions is not due to the intrinsic properties of HMdU, but is as a consequence of its removal by DNA repair enzymes [17,18] and subsequent errors arising during its repair [19]. Notably, HMdU is one of several recently discovered epigenetic modifications [11,13].…”
Section: Introductionmentioning
confidence: 99%